Effect of resistive load on the performance of an organic Rankine cycle with a scroll expander - Zhua, Jie; Chen, Ziwei; Huang, Hulin; Yan, Yuying (Elsevier, 2016)
An experimental investigation is performed for an organic Rankine cycle system with different electrical resistive loads. The test rig is set up with a small scroll expander-generator unit, a boiler and a magnetically coupled pump. R134a is used as the working fluid in the system. The experimental results reveal that the resistive load coupled to the scroll expander-generator unit affects the expander performance and power output characteristics. It is found that an optimum pressure ratio exists for the maximum power output. The optimal pressure ratio of the expander decreases markedly as the resistive load gets higher. The optimum pressure ratio of the scroll expander is 3.6 at a rotation speed of 3450 r/min for a resistive load of 18.6 Ω. The maximum electrical power output is 564.5 W and corresponding isentropic and volumetric efficiencies are 78% and 83% respectively.